A Psychosocial Development of a Young Adult Character in Thirteen Reasons Why Novel - Raden Nur Prasetyo Wibowo (Passage, 2019)
This study analyzes a young adult protagonist character Clay Jensen in Thirteen Reasons Why novel by Asher (2007). The present research investigates the main character’s psychosocial development. The novel tells a journey of Clay Jensen who struggles to listen to a series of tapes that reveal reasons why his crush, Hannah Baker, committed suicide in Hannah’s voice. The way Clay reflects his emotions and responses to the tapes interest the researcher to analyze his psychosocial development, specifically the psychological and social characteristics. The purposes of this study are to enlist Clay Jensen’s psychosocial issues and to discover how he copes with these issues as part of psychosocial development. This textual analysis applied Bucher and Hinton’s (2010) developmental characteristics of young adults; the analysis explored Clay Jensen’s narrative events that embody the ideas of psychosocial issues and how he deals with the psychosocial issues. It is concluded that Clay Jensen develops psychosocially because he experiences some psychosocial issues such as anxiety and low self-esteem, but he is able to cope with these issues. Clay Jensen is also a round character who develops himself from being selfish to be a more sympathetic person.